Ciclo multimodal complexo de leitura em língua francesa - Generoso, Lisa Paula (2016)
The objective of this research is to describe and interpret the phenomenon complex multimodal reading cycle in French, considering that multimodality is used to refer to different qualities of perception caused by different forms of sense production that involve different technologies, Rojo (2012) In this sense, multimodality suggests a look at five analytical methods: linguistic, visual, spatial, gestural and sonorous. The theoretical framework that supports this research is shaped by complexity, as envisioned by Morin (2006, 2009), reading from the multimodal perspective, as perceived by Rojo (2012), and the teaching of French as a Foreign Language, as conceived by Courtillon (2003). Methodologically, this study is grounded on the complex hermeneutic-phenomenological approach (AHFC), according to Freire (2007, 2010, 2012, 2015), who was initially based on van Manen (1990). This research engaged eight participants – beginners in the study of French as a foreign language - who work as public school teachers, dealing with various educational disciplines in various grades. The selection of these participants was motivated by the potential impact of the complex multimodal reading cycle on students of French, perceived by the researcher in her teaching experience. The research began with the identification of the participants’ profile, followed by classes that involved the reading of several classic texts. By the end of each class in which the complex multimodal cycle was developed, the participants produced “One minute Papers”, which revealed the way each one of them experienced this particular form of developing reading classes. The complex multimodal cycle of reading revealed that learning, knowledge, embarrassment, motivation, self-fulfillment, interest, and attention are the constructs that compound the phenomenon on focus in this study. This knowledge about the phenomenon becomes relevant since it may contribute to the development of the reading skill in French or other foreign languages in Brazil, inspiring further research and future applications